Identification of an Integrin α6‐Targeted Peptide for Nasopharyngeal Carcinoma‐Specific Nanotherapeutics. Issue 7 (26th April 2019) - Feng, Guo‐Kai; Zhang, Meng‐Qing; Wang, Hong‐Xia; Cai, Jing; Chen, Shu‐Peng; Wang, Qian; Gong, Jing; Leong, Kam W.; Wang, Jun; Zhang, Xing; Zeng, Mu‐Sheng
Abstract: Integrin α6 emerges as an attractive cancer therapeutic target. Here, the authors present for the first‐time, that integrin α6 is overexpressed in nasopharyngeal carcinoma (NPC) and serves as a prognostic predictor and a cancer stem cell (CSC) biomarker. An NPC‐targeted peptide CRWYDENAC (dubbed RWY) with high specificity and affinity for integrin α6 is identified, and an integrin α6‐targeted nanotherapeutic against NPC is developed by encapsulating a cisplatin prodrug Pt(IV) with RWY‐grafted polymeric nanoparticles (dubbed RWY‐NP/Pt(IV)). The delivery of cisplatin prodrug Pt(IV) by RWY‐NP/Pt(IV) results in an approximately 100‐fold increase in cytotoxicity over free cisplatin, as well as a 5‐fold increase over Scramble‐NP/Pt(IV) control. RWY‐NP/Pt(IV) suppresses NPC tumor growth with an inhibition rate of around 78%, compared with the 44% and 41% achieved by free cisplatin and Scramble‐NP/Pt(IV) treatment. Loss of body weight is observed in free cisplatin treated mice but not in RWY‐NP/Pt(IV) treated mice. Taken together, RWY‐NP/Pt(IV) enhances the therapeutic efficacy of cisplatin treatment and reduces deleterious side effects, suggesting the potential application of the integrin α6‐targeted RWY peptide for nanotherapeutics against NPC. Abstract : Integrin α6‐targeted nanoparticles for targeted therapy of nasopharyngeal carcinoma . The integrin α6‐targeted RWY peptide enhances cancer specific homing and penetrating ability, and the cisplatin pro‐drug Pt(IV) can be reduced to reactive and effective cisplatin Pt(II) within the reducing environment of cancer cells.